عائلی زندگی اور اُس کے مسائل سے متعلق ابنِ تیمیہ کے فقہی تفردات کا تجزیاتی مطالعہ: An analytical study of Ibn Taymiyyah's jurisprudential distinctions Regarding Family Life and its problems - Haq Turabi, Muhammad Fazal; Muhammad Fakhru Din, Hafiz (Al-Amīr Research Journal for Islamic Studies, 2022)
Marriage has been given the status of half-faith, based on which a family is formed, and society is established. Marriage is associated with issues of lineage and inheritance and a section of the Quran describes this subject. The jurists have explained in detail the issues of marriage, dowry, breastfeeding, 'iddah, and alimony under the book of marriage. Ibn Taymiyyah, like other jurisprudential issues, has differed from several jurists on issues related to marriage. For example, it is fair for a man to marry his wife's foster mother and foster daughter. Marriage can take place in any of the terms or words from which the meaning of marriage is derived. Like the father, the grandfather also has the right to marry a minor girl without her permission, it is permissible to marry, the wife has the right to terminate the marriage in case of defect in Haq-e-Mahr, etc. All such jurisprudential dissent will be explained with arguments so that one can be aware of Ibn Taymiyyah's dissent and the arguments behind it. KeyWords: Ibn e Taymiyyah, Jurisprudential Distinctions, Nikaḥ, Kitāb un-Nikaḥ Haq-e-Mahr.